ADVANTAGES OF LAPAROSCOPIC SURGICAL TREATMENT OF KIDNEYS IN CHILDHOOD (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article discusses the advantages of laparoscopic surgical treatment of kidneys in children. Laparoscopy has proven to be a minimally invasive method with a low complication rate and fast patient recovery. Data from scientific sources and databases of Google Scholar, Scopus and others are analyzed. The results show that laparoscopy has significant advantages over traditional open surgeries, such as reduced postoperative pain, a short rehabilitation period, and minimal trauma, making it the preferred method in pediatric urology.